Helen Thayer's Arctic adventure a woman and a dog walk to the North Pole - Isaacs, Sally Senzell 1950-; Sasheva, Iva (North Mankato, Minnesota Capstone Young Readers, 2016)
"A woman and a dog make their way to the magnetic North Pole on foot--the first trip of this nature"--
Adventures
Includes bibliographical references and index
1 2 13 15
Keywords: Thayer, Helen -- Travel -- Arctic regions -- Juvenile literature; Women explorers -- Juvenile literature; Arctic regions -- Description and travel -- Juvenile literature; North Pole -- Description and travel -- Juvenile literature